A mechanistic model for minimizing pressure loss in the wellbore during drilling by considering the effects of cuttings - Li, Baixue; Wang, Xueying; Zhang, Feifei; Wang, Xi; Wang, Yuezhi; Wang, Yidi (Frontiers in Earth Science, 2023)
Because of the existence of cuttings in the flow, the pressure loss in the wellbore can increase significantly. Minimization of the flow pressure loss greatly benefits the drilling process. This work investigates the most important factors to the pressure loss in the wellbore during the hole cleaning process. It is found that, for the solid–liquid, two-phase flow, the fluid flow rate is not always proportional to annular pressure loss as the single-phase flow. The mechanisms behind this effect are studied, and a mechanistic model based on the solid–liquid, two-phase flow is proposed to simulate the hole cleaning process and predict the critical fluid flow rate, which gives the minimum pressure loss in the wellbore. The effect of the inclination angle, fluid rheological parameters, annulus geometry, and the rate of penetration on the critical value are investigated by using the proposed model. Results show that the critical flow rate value increases as the inclination angle increases under 60° and decreases once the inclination angle goes beyond 60°. The critical flow rate increases as the fluid viscosity and the wellbore geometry increase. This proposed model can be used to minimize the pressure loss in the wellbore in the given operational conditions and optimize the drilling parameters.